Combined Analytical Py-GC-MS, SEM, FTIR and C-13 NMR for Investigating the Removal of Trace Metals from Aqueous Solutions by Biochar - De Andrade, Mineia A. M.; Monteiro, Adnivia S. C.; Gontijo, Erik S. J.; De Castro Bueno, Carolina; Macedo, Joao C. A.; Rangel, Elidiane C.; Melo, Darllene S.; Montero, Jose I. Z.; Rosa, Andre H. (Journal of the Brazilian Chemical Society, 2020)
In this study, the efficiency of biochar (BC) produced from sugarcane bagasse at different pyrolysis temperatures (300, 400, 500 and 600 degrees C) for simultaneous removal of Cd-II, Pb-II, Cu-II, Cr-III, Ni-II and Zn-II ions from aqueous solutions was assessed. All BC were characterized using scanning electron microscopy (SEM), Fourier transform infrared (FTIR). C-13 nuclear magnetic resonance (C-13 NMR) and pyrolysis-gas chromatography-mass spectrometry (Py-GC-MS). The effects of pyrolysis temperature, initial adsorbate concentration and adsorbent dosage on adorption capacity of BC were examined through batch experiments. The BC efficiency was also evaluated after a desorption cycle. The maximal adsorptions (C-II: 51.50%. Crm: 74.35%. Cu-III: 91.18%, Ni-II: 47.05%. Pb-II: 96.17% and Zn-II: 40.50%) were observed for BC produced at 500 degrees C, probably because of its higher porosity and presence of functional groups detected by SEM and FTIR. The maximum adsorption capacity for Cd-II, Cr-III, Cu-II, Ni-II and Zn-II (ions fitted to Langmuir model) were 175, 303, 455. 156 and 128 mu g g(-1). respectively. The predominance of phenolic groups observed in Py-GC-MS data may explain the high percentage of multi-element removal. Experimental data were best fitted to pseudo-second order, Sips and Freundlich models. The BC presented good removal results after a desorption cycle.
CRIS-Team WoS Importer:2020-06-30

Dominance of in situ produced particulate organic carbon in a subtropical reservoir inferred from carbon stable isotopes - De Castro Bueno, Carolina; Frascareli, Daniele; Gontijo, Erik S.J.; van Geldern, Robert; Rosa, André H.; Friese, Kurt; Barth, Johannes (Scientific Reports, 2020)
Sources of particulate organic carbon (POC) play important roles in aqueous carbon cycling because internal production can provide labile material that can easily be turned into CO2. On the other hand, more recalcitrant external POC inputs can cause increased loads to sedimentary organic matter that may ultimately cause CH4 release. In order to differentiate sources, stable isotopes offer a useful tool. We present a study on the Itupararanga Reservoir (Brazil) where origins of POC were explored by comparing its isotope ratios (δ13CPOC) to those of dissolved inorganic carbon (δ13CDIC). The δ13CPOC averaged around − 25.1‰ in near-surface waters, which indicates higher primary production inferred from a fractionation model that takes into account carbon transfer with a combined evaluation of δ13CPOC, δ13CDIC and aqueous CO2. However, δ13CPOC values for water depths from 3 to 15 m decreased to − 35.6‰ and indicated different carbon sources. Accordingly, the δ13CDIC values of the reservoir averaged around + 0.6‰ in the top 3 m of the water column. This indicates CO2 degassing and photosynthesis. Below this depth, DIC isotope values of as low as − 10.1‰ showed stronger influences of respiration. A fractionation model with both isotope parameters revealed that 24% of the POC in the reservoir originated from detritus outside the reservoir and 76% of it was produced internally by aqueous CO2 fixation.
CRIS-Team Scopus Importer:2020-08-14

Statistical Approaches Link Sources of Sediment Contamination in Subtropical Reservoirs to Land Use: an Example from the Itupararanga Reservoir (Brazil) - Frascareli, Daniele; Gontijo, Erik Sartori Jeunon; Silva, Sheila Cardoso; Melo, Darllene Silveira; De Castro Bueno, Carolina; Simonetti, Vanessa C.; Barth, Johannes; Carlos, Viviane Moschini; Rosa, Andre Henrique; Friese, Kurt (Water Air and Soil Pollution, 2022)
The identification and characterisation of diffuse pollutant sources in reservoirs remain a challenge due to the complexity of catchments with their variety of land use types. A sediment fingerprinting approach was used in this investigation for determining the sources of contaminants in sediments. By using this approach, we demonstrated how the effects of land use on pollution load of the subtropical Itupararanga Reservoir in Brazil can be de-convoluted. Sediments were collected at seven sampling sites (S1–S7) over the length of the reservoir. This was matched by eight sampling sites (P1–P8) of soils from different land use types (agriculture, urban and forest). Investigated parameters included grain size, total nitrogen (TN), total phosphorus (TP), total carbon (TC), organic matter by loss on ignition (OM), total sulphur (TS), and major ions and metals (Ca2+, Mg2+, Na+, K+, NH4+, SO42−, Cl−, NO3−, As, Al, Ba, Cr, Cu, Fe, Mn, Ni and Zn). Our fingerprinting approach helped to outline horizontal spatial heterogeneities (categorised as riverine, transitional and lacustrine areas) that were attributed mainly to sand (> 26.7%), Si (569 g kg−1) and Cr (336 mg kg−1) at S1 (riverine area). Moreover, fine particles of silt and clay leached from agricultural activities were enriched with OM, TP, TN, TC, As and Cr. These types of sediments were deposited into transitional and lacustrine areas. Furthermore, urban soils were a source of sand and phosphorus to sediments. The fingerprinting method reduced the number of relevant parameters for source identification and helped to identify non-point sources of sediments.
CRIS-Team Scopus Importer:2022-04-29
Keywords: Land use; Non-point pollution sources; Sediment fingerprinting approach; Spatial heterogeneity; Subtropical reservoirs